Dwarf galaxies at low and high redshift. Issue Volume 14:Issue S344(2019) (August 2018) - Kong, Xu; Lian, Jianhui; Gao, Yulong; Chen, Zuyi; Chen, Guangwen; Lin, Zesen; Liu, Haiyang
Abstract: The overwhelming majority of galaxies in the Universe are dwarf galaxies. But although they are important components in understanding galaxy evolution, these systems are typically too faint to be observed at high redshifts. However, we are able to obtain an unobscured view of early star formation and chemical enrichment in these galaxies at low redshift and low-redshift analogs at high redshift. In this talk, I will review the mass-metallicity relation, the mass-star formation rate relation of galaxies, the classifications of dwarf galaxies, and the importance of dwarf galaxies for both astronomy and physics. Then I will introduce some work in our group on connections among between different types of dwarf galaxies, the mass-metallicity relations and the main sequence relations of dwarf galaxies, using the deep optical and near infrared images and spectra of large dwarf galaxy sample. At the end, I will talk about some projects of dwarf galaxies we are working on, including the spectroscopic survey for compact dwarf galaxies using the LAMOST.